Teacher presence as mediator in online learning: the case for French as a foreign language - Mohd Taib, Nor Azhar; Rahmat, Noor Hanim; Ismail, Saidah; Hassan @ Hussin, Omrah (Open Access Publishing Group, 2021)
Fortunately, technology and long entered the education sectors when the world is faced with the pandemic. Whether teachers and learners are ready or not, online classes are here to stay. Online learning is a unique way of learning that allow flexibility at many levels. Language educators once felt that the learning of language can only be done face-to-face because of the needs of some language skills. This study is done to explore the portrayal of presence during online learning of the French as a foreign language. This quantitative study is done to investigate how learners cope learning French online. 170 respondents were purposely chosen from learners who took French as a foreign language. They attended the course in a few public and private universities. The instrument used is a questionnaire. Findings revealed interesting influence of the teacher as mediator in online learning.